Towards (Unilateral) Recognition of “the Technological Other”​ – Vulnerability, Resistance and Adequate Regard - Juchniewicz, Natalia (ETHICS IN PROGRESS, 2024)
The aim of the article is to answer the question of whether the theory of recognition can be applied to research on the human-technology relationship and, if so, to what extent. The article assumes that the theory of recognition is a normative theory, and therefore, its moral consequences can certainly be applied to human persons. To use this theory for studying the relationship between humans and technology, shifts in the theory are necessary. These shifts have been reduced to the concept of solidarity with technological artifacts (especially with robots). However, the article constructs an argument that the concepts of vulnerability and resistance may be helpful in justifying the development of recognition in the relationship between humans and technology. The model of recognition discussed in this case is not, however, a model based on mutual relations but rather on unilateral recognition, which is introduced into the theory through the concept of adequate regard.